Urgensi Supervisi Digital di Era Pasca-Pandemi : Tinjauan Literatur terhadap Teori dan Praktik Supervisi Berbasis Teknologi - Puspitasari, Ni Luh Gede Dian; Anita, Anita; Wulandari, Yuli; Warman, Warman; Masrur, Masrur (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
The rapid advancement of technology during and after the COVID-19 pandemic has driven significant changes in educational supervision practices. Traditional, face-to-face supervision has evolved into digital formats using various online platforms to improve the efficiency and effectiveness of teacher development. This literature review investigates the current theoretical frameworks and practical implementations of digital supervision in the post-pandemic era. The study employs a qualitative approach using content analysis of scholarly literature published between 2020 and 2025, sourced from databases such as Scopus, Google Scholar, and DOAJ. The findings reveal that digital supervision holds substantial potential to improve the quality of education through more flexible, data-driven, and collaborative monitoring approaches. However, several challenges persist, including limited digital literacy among educators, inadequate technological infrastructure in rural areas, and the absence of a standardized national policy regulating digital supervision practices. The review highlights the need for systematic, inclusive, and sustainable digital supervision models, supported by strong policy frameworks and professional development programs. These models include LMS-based supervision, hybrid formats, virtual collaboration networks, and data-driven approaches that incorporate real-time performance analytics. The study concludes that digital supervision should no longer be considered a temporary solution but a strategic component of future educational quality assurance systems.